Correlation of Permeability and Thickness of the Clay Core Zone on Plastic Deformation in the Melawi Dry Dam, Indonesia - A Raya Diva Oriana; Anggara Wiyono Wit Saputra; Andre Primantyo Hendrawan (Postgraduate, University of Mataram, 2026)
The Melawi Dry Dam is a zoned embankment dam with clay core located in West Kalimantan, Indonesia. As a flood-control structure, it undergoes significant wet–dry cycles that modify stress distribution and pore water pressure, potentially influencing plastic deformation within the core zone. This study aims to evaluate the effects of clay core thickness and permeability coefficient on vertical plastic deformation using a combination of fully coupled flow–deformation and plastic analysis in PLAXIS 2D. Numerical simulations represent a post-flood condition followed by a 130-day consecutive dry season period, defined as Julian days when rainfall remains at the lower rainfall-gradient threshold, during which the reservoir remains empty because inflow exceeds outlet capacity. Nine scenarios were analyzed by combining three core thicknesses (11.64, 19.40, and 27.16 m) with three laboratory-determined permeability coefficients. The results indicate that seven scenarios remain below the maximum allowable deformation limit of 1.0% of the dam height. Statistical analysis shows a strong correlation between core thickness, permeability, and deformation (R = 0.929). Multiple linear regression (Significance F = 0.00253; p < 0.05) confirms that both variables significantly affect deformation. Increasing core thickness consistently reduces plastic deformation, while lower permeability enhances resistance to seepage-induced instability, thereby supporting safe dry dam design.